Acanthoic Acid Can Partially Prevent Alcohol Exposure-Induced Liver Lipid Deposition and Inflammation - Yao, You-Li; Han, Xin; Li, Zhi-Man; Lian, Li-Hua; Nan, Ji-Xing; Wu, Yan-Ling (Frontiers in Pharmacology, 2017)
Aims: The present study aims to detect the effect of acanthoic acid (AA) on alcohol exposure-induced liver lipid deposition and inflammation, and to explore the mechanisms. Methods: C57BL/6 mice were pretreated with single dose of AA (20 and 40 mg/kg) by oral gavage or equal volume of saline, and then exposed to three doses of ethanol (5 g/kg body weight, 25%, w/v) by gavage within 24 h. The mice were sacrificed at 6 h after the last ethanol dosing. Serum and hepatic indexes were detected by western blot, RT-PCR, and histopathological assay. AML-12 cells were pretreated with AA (5, 10, 20 μM), or AICAR (500 μM), GW3965 (1μM), SRT1720 (6μM), Nicotinamide (20mM) for 2 h, respectively, and then following treated with EtOH (200mM) and lipopolysaccharide (LPS) (10ng/ml) for additional 48 h. Cell protein and mRNA were collected for western blot and RT-PCR. Cytokines interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) release were detected by ELISA assay. Results: It was found that AA significantly decreased acute ethanol-induced increasing of the serum ALT/AST, LDH, ALP levels, and hepatic and serum triglyceride levels, and reduced fat droplets accumulation in mice liver. AA significantly suppressed the levels of sterol regulatory element binding protein 1 (SREBP-1), cytochrome P4502E1 (CYP2E1), IL-1β, and caspase-1 induced by ethanol. Furthermore, a significant decline of sirtuin 1 (Sirt1) and liver X receptors (LXRs) levels was observed in EtOH group, compared with normal group mice. And AA pretreatment increased the Sirt1 and LXRs levels, and also ameliorated phosphorylation of liver kinase B-1 (LKB1), adenosine monophosphate-activated protein kinase (AMPK), acetyl CoA carboxylase (ACC) proteins, compared with EtOH group. However, the levels of peroxisome proliferator activated receptor -α or -γ (PPAR-α or PPAR-γ) induced by acute ethanol were reversed by AA. In EtOH/LPS cultivated AML-12 cells, AA decreased IL-1β and TNF-α levels, lipid droplets, and SREBP-1 and CYP2E1 expressions, compared with EtOH/LPS treatment. AA also significantly increased protein expressions of Sirt1, p-LKB1, p-ACC, PPARα, and decreased protein expression of PPARγ, compared with EtOH/LPS treatment. Conclusions: AA can partially prevent alcohol exposure-induced liver lipid deposition and inflammation via regulation of LKB1/Sirt1/AMPK/ACC and LXRs pathways.